Avicenna’s Canon of Medicine and Modern Urology: Part II: Bladder Calculi - Madineh, Sayed Mohammad Ali (Urology Journal, 2009)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!-- /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; text-align:right; mso-pagination:widow-orphan; direction:rtl; unicode-bidi:embed; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-bidi-language:FA;} @page Section1 {size:612.0pt 792.0pt; margin:72.0pt 90.0pt 72.0pt 90.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]--> In the previous issue of the Urology Journal, a comparison of Avicenna’s Canon of Medicine with modern urologic findings was done in part I of this article, addressing bladder anatomy and physiology and bladder calculi. In part II of this review, the remaining chapters of the Canon of Medicine on bladder calculi are reviewed. Avicenna points to perineal urethrostomy (preineostomy), which is today performed as the last therapeutic line or as a temporary remedy before surgical treatment. He also describes surgery via transperineal route and warns the surgeon of the proximity of vasa deferentia, prostate gland, and neurovascular bundle and their exposure in this position. Usage of grasping forceps for removal of bladder calculus and emphasis on removing all calculus fragments are the interesting points of this chapter. Avicenna explains a technique similar to the use of a babcock for prevention of calculus migration. Complications of bladder calculus surgery and cystostomy are also addressed with scientific precision in the Canon.